The Effect of Using Matching Word Game Towards Students’ Vocabulary Mastery at SMP Negeri 4 Ujungbatu - Purba, Friska Ratna Sari; Aryuadi, Aryuadi; Fakhruzi, Fakhruzi (Jurnal Pendidikan Tuntas, 2023)
This experimental research was carried out in the eighth grade at MTs Muhammadiyah Tanjung Belit Airtiris. This study aims to determine the effect of Matching Word Game on students' vocabulary mastery. This research methodology uses a quasi-experimental design. The sample of this study was class VII A as the experimental class and VII B as the control class. The experimental class consisted of 17 students and the control class consisted of 17 students. The instrument used in the study was a vocabulary test. Data analysis used the SPSS 25 program. Based on the results of the study, the average score of students in the experimental class was 65.15 and 52.15 in the control class. Data analysis showed a significance (2-tailed) 0000 < 0.05 which means Ha is accepted. The key is that there is an effect on the use of the Matching Word Game on students' vocabulary mastery. Keyword: Vocabulary Mastery, Quasi Experimental, Matching Word Game